á¹¬ULÅªâ€™ AL-HILÄ€L Rekonstruksi Konsep Dasar HilÄl - Aris, Nur (Al-Ahkam, 2014)
This paper intends to review the basic concepts of crescent issue as the most fundamental concepts of the Hijri calendar systems. The crescent basic concept of á¹ulÅ«â€˜ al-hilÄl, based on these principles: first, put the crescent as a matter of objective existence does not depend on the subject or observer, but the object itself. Second, the lower moon extremity as a conceptual reference for basic concepts. Third, the beginning of the lunar calender is based on crescent moon rising. This paper also tries to determine the cause of the beginning of lunar calender with the normative traditions of the prophet to analyze the visual sighting of the crescent and istikmÄl from the philosophy of Islamic Lawâ€™s point of view. Normative cause of fasting Ramadan is not obligatory visual sighting of the crescent of Ramadan, but the rising of the crescent (á¹ulÅ«â€˜ al-hilÄl). Visual sighting of the crescent and istikmÄl and also Astronomy is a way to find out and make sure that the cause has occurred and they are not the cause by itself